Power system security improvement using an OPA model and IPSO algorithm. (March 2020) - Hasanvand, Saeed; Fallahzadeh-Abarghouei, Hossein; Mahboubi-Moghaddam, Esmaeil
The growing demand for power generation makes power systems increasingly more complex to operate and less secure against outages, so the risk of extensive blackouts is growing and needs to be addressed. Cascading failures are the main reason for extensive blackouts, so to investigate this effect a new method including a standard blackout model, named ORNL-PSerc-Alaska (OPA), and static synchronous series compensator (SSSC) placement using an improved particle swarm optimization (IPSO) algorithm is proposed. This study provides two optimization approaches and presents optimal corrective actions. The results will help operators to implement corrective actions like optimal generation and load redispatching to return the system to a stable operating condition. The effectiveness of the proposed model is demonstrated using a realistic transmission network. Simulation results show a significant effect of SSSC on decreasing the risk of cascading failures and the ability of the proposed method to prevent blackout.